Cocoa polyphenols and milk proteins: covalent and non-covalent interactions, chocolate process and effects on potential polyphenol bioaccesibility - Dalabasmaz, Sevim; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat (TAYLOR & FRANCIS INC, 2024)
In this study, we discussed covalent and non-covalent reactions between cocoa polyphenols and proteins (milk and cocoa) and the possible effects of these reactions on their bioaccessibility, considering environmental and processing conditions. Better insight into these interactions is crucial for understanding the biological effects of polyphenols, developing nutritional strategies, and improving food processing and storage. Protein-polyphenol reactions affect the properties of the final product and can lead to the formation of various precursors at various stages in the manufacturing process, such as fermentation, roasting, alkalization, and conching. Due to the complex composition of the chocolate and the various technological processes, comprehensive food profiling strategies should be applied to analyze protein-polyphenol covalent reactions covering a wide range of potential reaction products. This will help to identify potential effects on the bioaccessibility of bioactive compounds such as low-molecular-weight peptides and polyphenols. To achieve this, databases of potential reaction products and their binding sites can be generated, and the effects of various process conditions on related parameters can be investigated. This would then allow to a deeper insight into mechanisms behind protein-polyphenol interactions in chocolate, and develop strategies to optimize chocolate production for improved nutritional and sensory properties.
Keywords: Chocolate; cocoa; polyphenol; protein; THEOBROMA-CACAO L.; GREEN TEA POLYPHENOLS; BOVINE SERUM-ALBUMIN; BETA-LACTOGLOBULIN; ANTIOXIDANT PROPERTIES; DARK CHOCOLATE; IN-VITRO; (-)-EPIGALLOCATECHIN GALLATE; PHENOLIC-COMPOUNDS; PLANT PHENOLICS; Food Science & Technology; Nutrition & Dietetics